Современный подход к организации работы санитарно-карантинных отделов - Коваль, А.А.; Рыбак, И.Т.; Мироненко (Актуальні проблеми транспортної медицини, 2005)
Авторами статьи изучена организация работы санитарно-карантинных отделов СЭС Днепровского бассейна, предложен современный подход к профессиональной подготовке медицинского персонала для работы в СКО и указаны недостатки существующих нормативных документов по оценке качества питьевой воды на судах. The authors have learnt the organization of the work of sanitary - and - quarantine units ( SQU )of sanitary - and - epidemiologic stations departments of the Dnieper Basin. Some approaches to the professional training of SQU future employees are given. Besides the authors highlighted several drawbacks in the existing normative documents concerning the quality of a drinking water on a board and the methods of its estimation.